2012
DOI: 10.4028/www.scientific.net/amr.621.31
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Graphene/Polyamide 6 Composites by Melt Compounding

Abstract: In this paper, graphene was obtained by Oxidation-reduction method. The obtained graphene was characterized by XRD and FTIR. On this basis, graphene/polyamide 6(PA6) composites were prepared by melt compounding. The well-dispersed graphene nanosheets in PA6 matrix was investigated by SEM. The properties were characterized by XRD, DSC and TGA. The results showed that the α-phase of polyamide 6 induced into γ-phase by adding graphene. The crystallization temperature and the crystallinity of composites have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…These results demonstrated that the thermal stability of the sample by adding graphene has increased, compared to the neat and other samples. This is due to the presence of graphene particles with large surface area that act as barrier and a thermal insulation [1]. The TGA results are similar to previous researches [1,6,19] However, we observed higher degradation temperature and thermal stability in samples with graphite and carbon black compared to M6 sample due to the intensifying effect of these fillers, but the difference is negligible.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…These results demonstrated that the thermal stability of the sample by adding graphene has increased, compared to the neat and other samples. This is due to the presence of graphene particles with large surface area that act as barrier and a thermal insulation [1]. The TGA results are similar to previous researches [1,6,19] However, we observed higher degradation temperature and thermal stability in samples with graphite and carbon black compared to M6 sample due to the intensifying effect of these fillers, but the difference is negligible.…”
Section: Resultssupporting
confidence: 79%
“…This reduction continued with increasing graphene content up to 3% (N3). This process has been observed in the works of other researchers on pure polyamide [1,6]. Graphene sheets with high aspect ratio (surface area to thickness) easily penetrate through polyamide chains and cause interruption in crystallization process.…”
Section: Characterizationmentioning
confidence: 71%
See 2 more Smart Citations
“…[1][2][3][4] The polymers based nanocomposites incorporated with graphite and graphitic nano fillers have shown substantial improvement in mechanical, thermal, electrical properties. [5][6][7][8][9][10][11][12][13][14] While the graphene used for barrier membrane applications exhibited excellent impermeability to oxygen and effective optical property together with ultrahigh electron mobility. [15][16][17] The nanocomposites based on exfoliated graphite nanoplatelets (xGnPs) showed considerable improvement in mechanical, thermal, electrical and thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%